COUNSELLING HOMICIDAL AND SUICIDAL CLIENTS: ETHICAL CLARITY ON DUTY TO WARN - Janet Ann Fernandez; Poh Li Lau; Diana-Lea Baranovich (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Although, breaching confidentiality have become synonymous with unethical counselling practice, fellow counsellors need to understand their code of ethics and the exceptions to confidentiality which includes the need disclose confidential information if the client poses a danger to self or others. These clients may pose a serious threat of violence with the intention to physically harm himself/herself or another identifiable individual. It is one of the few circumstances in which the counsellor is obliged to breach confidentiality and notify the relevant authorities in order to prevent any foreseeable danger. The aim of this paper is to discuss the clinically realistic views, strategies and the need to breach confidentiality when dealing with potentially dangerous clients. This paper introduces an ethical-decision making model for Malaysian counsellors to use as a guide. It also includes four case studies of various dangerous situations that may arise in which counsellors may need to disclose the confidential information to relevant authorities. In a nutshell, a counsellor should report the dangerousness of a client to relevant parties when; (i) the client must have made clear, serious and specific threat of violence; (ii) the specific threats must have been directed to an identifiable and specific victim; (iii) there is a counsellor-client relationship, a special relationship between the counsellor and client must exist. When all these conditions are present, the counsellor holds a duty to disclose to the extent necessary to the appropriate parties in order to protect the client and identified others from danger.